You are on page 1of 3

1 Stress from axial loads on the End Disk 1

1 Stress from axial loads on the End Disk
Consider End Thrust on Disc of Pulley
The thrust on the end disk can come from a misaligned pulley where the
load or from the design or the installation of the locking assembly itself.
As the locking assembly, as shown in Fig xx, is tightened it will first stop
slipping on the shaft. Additional tightening the draws the end disk outwards
causing a bellowing load. For this style of locking assembly the recommended
installation sequence is to tighten one end of the pulley prior to tightening the
second end. Failure to due this may cause twice the amount of load from the
bellow.
As both of these potential loadings are in a single direction they generally
not considered to cause alternating loads.
The typical axial load from belt misalignment to consider if 10% of the total
belt tension H = 10% x (T1 + T2). This load is then evenly divided between
the two end disks.
Lange (page 71) derives the stress from a thrust on the end disk as
σ
r
=
by Omer Bladgett (1961), Lincoln Electric.
Consider disc as outer edge fixed and supported. Inner edge fixed.
Inner edge (hub)
Max σ
r
=
3W
2πt
2
_
1 −
2r
2
r
2
−r
2
1
log
r
r1
_
Max ∆ =
27W
400πEt
3
_
r
2
−r
2
1

4r
2
r
2
1
r
2
−r
2
1
_
log
r
r1
_
2
_
or use
σ
r
=
K1W
t
2
∆ =
K2Wr
2
Et
3
r
r1
K
1
K
2
1.25 0.115 0.00129
1.5 0.220 0.0064
2.0 0.405 0.0237
3.0 0.703 0.062
4.0 0.933 0.092
5.0 1.13 0.114
Adapted from Timoshenko ”Theory of Plates and Shells” and Roark ”For-
mulas for Stress and Strain”
1.1 Symmetrical Bending - Lange
Nw+
∂N
∂r
_
2

3
w
∂r
3
+
2 + ν
r

2
w
∂r
2

1
r
2
∂w
∂r
+
2
r
2

3
w
∂r∂φ
2

3
r
3

2
w
∂φ
2
_
+

2
N
∂r
2
_

2
w
∂r
2
+
ν
r
∂w
∂r
+
1
r
2

2
w
∂φ
2
_
= 0
(1)
where
w =

2
w
∂r
2
+
1
r
∂w
∂r
+
1
r
2

2
w
∂φ
2
N =
Eh
3
12(1−ν
2
)
1 Stress from axial loads on the End Disk 2
The boundary conditions on the edges of the end plates of a conveyor belt
pulley loaded by the axial component of the belt tension are:
on the inner boundary: r = r
i
, w

= 0
on the outer boundary: r = r
a
, w

= 0
p
ra
=
H/2
2πra
i.e. a transverse load p
r
a on the outer boundary and an axial load H
(clamped support inside and outside)
These boundary conditions can be expressed by the premises w = R(r);
∂w
∂φ
=
0 for equation (1).
With this, equation (1). can be transposed into the following form:

4
w
∂r
4
N+

3
w
∂r
3
_
2
r
N + 2N

_
+

2
w
∂r
2
_

1
r
2
N +
2 + ν
r
N

+ N

_
+
∂w
∂r
_
1
r
3
N −
1
r
2
N

+
ν
r
N

_
= 0
(2)
Introducing the following functions: N/N
0
= f(ρ); h
0
ξ = w; ρ = r/r
a
equa-
tion (2) will be transformed into:
ξ

ρ
4
f(ρ)+ξ

ρ
3
[2f(ρ)+2ρf

(ρ)]+ξ

ρ
2
[−f(ρ)+(2+ν)ρf

(ρ)+ρ
2
f

(ρ)]+ξ

ρ[f(ρ)−ρf

(ρ)+νρ
2
f

(ρ)] = 0
(3)
Assuming that the cross section is characterized by a function of the radius
in this manner:
(h/h
0
)
3
= f(ρ) = (ρ/ρ
i
)
n
; ρf

(ρ) = nf(ρ);
then equation (3) will be transformed into:
ξ

ρ
4

ρ
3
[2+2n]+ξ

ρ
2
[−1+(2+ν)n+n(n−1)]+ξ

ρ[1−n+νn(n−1)] = 0 (4)
The order of this equation can be reduced by setting n = ξ

which allows a
solution with n = ρ
q
. The solution of equation (4) reads then for n=0;
ξ = A
1
+ A
2
ρ
2
+ A
3
ρ
2
ln ρ + A
4
ln ρ
for n = 0; n = 2
ξ = A
1
+ A
2
ρ
q2
+ A
3
ρ
q3
+ A
4
ρ
q4
with
q
2
= 2 −n
q
3
= 1 −
1
2
(n −
_
n
2
+ 4(1 −νn)) = 1 −a
q
4
= 1 −
1
2
(n +
_
n
2
+ 4(1 −νn)) = 1 −b
The relations for the moment and transverse forces are:
m
r
= −
Nha
r
2
a

+ νρ
−1
ξ‘]
m
ψ
= −
Nha
r
2
a
[νξ

+ ρ
−1
ξ‘]
p
r
= −
Nha
r
2
a

+ ξ

ρ
−1
(1 + n) −ξ‘ρ
−2
(1 −νn)]
1 Stress from axial loads on the End Disk 3
From the above mentioned boundary conditions result the defining equations
for the coefficients A
2
, A
3
, and A
4
. Substituting these, the stresses can be
calculated as follows: n=0
σ
r
=
H
h
2
o
3(1 + ν)

_
ln ρ
i
ρ
−2
i
−1

1
2
+
3 + ν
2(1 + ν)
+ ln ρ +
1 −ν
1 + ν
ln ρ
i
ρ
−2
i
−1
ρ
2
_
(5)
σ
ψ
=
H
h
2
o
3(1 + ν)

_
ln ρ
i
ρ
−2
i
−1

1
2
+
1 + 3ν
2(1 + ν)
+ ln ρ −
1 −ν
1 + ν
ln ρ
i
ρ
−2
i
−1
ρ
2
_
(6)
τ = 0 (7)
for n = 0; n = 2
σ
r
=
H
h
2
o
_
ρ
ρ
i
_

2n
3
3
2πn(1 −ν)
_
(n −1 −ν) −
1 −ρ
1−a
i
1 −ρ
b−a
i
(a −ν)ρ
b−1

1 −ρ
1−b
i
1 −ρ
a−b
i
(b −ν)ρ
a−1
_
(8)
σ
ψ
=
H
h
2
o
_
ρ
ρ
i
_

2n
3
3
2πn(1 −ν)
_
[ν(n −1) −1) −
1 −ρ
1−a
i
1 −ρ
b−a
i
(νa −1)ρ
b−1

1 −ρ
1−b
i
1 −ρ
a−b
i
(νb −1)ρ
a−1
_
(9)
τ = 0 (10)
with
a =
1
2
(n −
_
n
2
+ 4(1 −νn))
b =
1
2
(n +
_
n
2
+ 4(1 −νn))